2012
DOI: 10.2190/ec.47.4.d
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Teaching Methods and Learning Style on Learning Program Design in Web-Based Education Systems

Abstract: The instructional value of web-based education systems has been an important area of research in information systems education. This study investigates the effect of various teaching methods on program design learning for students with specific learning styles in web-based education systems. The study takes first-year Computer Science and Information Engineering majors as the sample population. In an earlier study (Hung & Huang, 2008), Bayesian Network analysis of experimental data showed that students with "I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…This is a requirement of a permanent education, that is, an education for life (Biesta, 2015). Through the effective and efficient use of LS, the demands of the social context interact with the personal characteristics of the students (Aguilera-Pupo & Ortiz-Torres, 2009;Hung, 2012;Wei, Moreau, & Jennings, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…This is a requirement of a permanent education, that is, an education for life (Biesta, 2015). Through the effective and efficient use of LS, the demands of the social context interact with the personal characteristics of the students (Aguilera-Pupo & Ortiz-Torres, 2009;Hung, 2012;Wei, Moreau, & Jennings, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In his compilation of 800 meta-analyses into which more than 50,000 studies were included Hattie provides information on the influences on learning with respect to six domains: Contributions of the learner, the parental home, the school, the instructor, the curricula and teaching. In particular, the domain of teaching [24, The search through journals and conference reports on computer science education (Journal of Educational Computing Research, Computer Science Education, ACM Transaction on Computing Education, Special Interest Group Computer Science Education Bulletin) provided findings related to computer science education in regard to constructivist teaching activities [25], the "eXtreme teaching" approach [2], holistic teaching and learning [23], the influence of instructional methods on the design of computer programs [26], the effect of games on motivation in teaching [27], the application of formal modeling [28], the effectiveness of two-person team programming [29] and the application of the experiment [30].…”
Section: B Teaching Methodsmentioning
confidence: 99%
“…The study used the Felder and Silverman (1988) model that includes five dimensions: processing (active/reflective), perception (sensing/intuitive), input (visual/verbal), understanding (sequential/global), and organization (inductive/deductive). Hung (2012) focused on only two styles, inputoriented and perception-oriented, because a previous survey had suggested that students with these styles performed more poorly in program design courses. For students who were identified as input-oriented (visual/verbal), a diagram-based instructional method was adopted.…”
Section: Experimental Research Supporting the Learning Styles Hypothesismentioning
confidence: 99%